HNF1β, LHX1, and GGNBP2 deletion contributed to kidney and reproductive dysfunction in 17q12 deletion syndrome: evidence from a case report - Song, Chun-Yu; Yang, Jing; Jiang, Sheng; Du, Guo-Li (Frontiers in Genetics, 2024)
17q12 deletion syndrome is a chromosome abnormality in which there is a small missing piece (deletion) of genetic material on the long arm (q) of chromosome 17. Sign and symptoms can vary widely among different patients. Recently, a patient was diagnosed 17q12 deletion syndrome in our hospital and the clinical characteristics presented as absence of the right kidney, compensatory hypertrophy of the left kidney, multiple small cysts in the left kidney, pancreatic atrophy, hypomagnesemia, bowed uterus, multiple follicular cysts in both lobes of the thyroid gland, and Maturity-Onset Diabetes of the Young type 5 (MODY-5). A 1.5-Mb deletion with haploinsufficiency for 20 genes within the 17q12 region was found through copy number variation (CNV) analysis based on metagenomic Next-Generation Sequencing (mNGS) technology. Besides HNF1B absence, The LIM-class homeobox 1 transcription factor (LHX1) and GGNBP2 absences were also involved in regulation of kidney development and reproductive system through bioinformation analysis. The inheriting risk of 17q12 deletion syndrome is about 50%, and it is recommended to provide genetic counseling to all patients who are suspected or diagnosed with the syndrome.